2014
DOI: 10.3324/haematol.2014.108407
|View full text |Cite
|
Sign up to set email alerts
|

Favorable impact of natural killer cell reconstitution on chronic graft-versus-host disease and cytomegalovirus reactivation after allogeneic hematopoietic stem cell transplantation

Abstract: Acute GVHD grades 0-1 (n=219) Acute GVHD grades 2-4 (n=202)Bone marrow transplantation (n=99) Peripheral blood stem cell transplantation (n=323) AcuteGVHD 0-1, NK ≤ 111.7 (n=60) AcuteGVHD 2-4, NK ≤ 111.7 (n=80) AcuteGVHD 0-1, NK > 111.7 (n=84) AcuteGVHD 2-4, NK > 111.7 (n=48) AcuteGVHD 0-1, NK ≤ 111.7 (n=19) AcuteGVHD 2-4, NK ≤ 111.7 (n=23) AcuteGVHD 0-1, NK > 111.7 (n=25) AcuteGVHD 2-4, NK > 111.7 (n=23)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 48 publications
2
40
0
5
Order By: Relevance
“…[33][34][35] The ability of donor T cells to enhance early NK-cell functional maturation in the clinic is unclear, but may be related to the provision of relevant cytokines such as IL-2, IL-12, or IL-18 from numerous sources. 36 This is in contrast to the impact of GVHD on NK-cell numbers, where a clear deficiency exists 37,38 and indeed NK-cell deficiency has been suggested as a biomarker for GVHD, 39 although mechanisms are hitherto unknown. Our data show that during GVHD, competition between alloreactive T cells and NK cells for IL-15 results in impaired reconstitution of donor NK cells, with most remaining being early immature NK cells that are known to survive at low levels of IL-15.…”
Section: Discussionmentioning
confidence: 58%
“…[33][34][35] The ability of donor T cells to enhance early NK-cell functional maturation in the clinic is unclear, but may be related to the provision of relevant cytokines such as IL-2, IL-12, or IL-18 from numerous sources. 36 This is in contrast to the impact of GVHD on NK-cell numbers, where a clear deficiency exists 37,38 and indeed NK-cell deficiency has been suggested as a biomarker for GVHD, 39 although mechanisms are hitherto unknown. Our data show that during GVHD, competition between alloreactive T cells and NK cells for IL-15 results in impaired reconstitution of donor NK cells, with most remaining being early immature NK cells that are known to survive at low levels of IL-15.…”
Section: Discussionmentioning
confidence: 58%
“…22 Kheav et al demonstrated that a high NK cell count at month 3 was associated with a lower incidence of cGVHD. 23 Functional analysis further demonstrated that expanded CD56 bri NK cells retained IFNg production, which is known to promote antimicrobial immunity through the maturation of dendritic cells and the induction of Th1 responses. 24,25 Our previous study also found that rapid reconstitution of CD56 bri NK cells was associated with a lower TRM post-transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…38 In the setting of HSCT, several studies have addressed the role of CMV on immune recovery. 35,[39][40][41][42] However, none of these have provided multivariate evidence of the dominant role of CMV in shaping immune reconstitution, compared to pre-transplant characteristics, and to occurrence of GvHD. Further studies on a larger set of healthy controls are required to compare this pattern to that associated to CMV seropositivity in immunocompetent hosts.…”
Section: Discussionmentioning
confidence: 99%